Akbar or Aurangzeb? Ethics, Empire, and Print Publics in Colonial India. Issue 2 (August 2020) - Denault, Leigh
Abstract: In the 1870s, Indian news editors warned their readers of a series of crises threatening India. They saw the famines, wars, and poverty that they were describing as symptoms of the same illness: Colonial governors had failed to implement an ethical system of governance, and had therefore failed to create a healthy body politic, choosing to expend energy in punishing or censoring dissent when they should have been constructing more durable civic institutions. In North India, earlier Mughal traditions of political philosophy and governance offered a template to critique the current state. In drawing on these traditions, editors linked multiple registers of dissent, from simple 'fables' about emperors to more sophisticated arguments drawn from newly reinterpreted akhlaq texts, creating a print record of the multilingual, multivalent literary and oral worlds of Indian political thought. The figures of the Mughal emperors Akbar and Aurangzeb, representing the zenith and nadir of Mughal sovereignty, in turn linked popular and learned discussions on statecraft, good governance, and personal responsibility in an age of crisis. The press itself became a meeting point for multivalent discourses connecting South Asian publics, oral and literate, in their exploration of the nature of just rule in the context of empire, calling, in the process, new 'publics' into being.